Marie, dancing - Meyer, Carolyn, 1935- (Harcourt, 2005)
A fictionalized autobiography of Marie Van Goethem, the impoverished student from the Paris Opera ballet school who became the model for Edgar Degas's famous sculpture, "The Little Dancer.".